Genetic dissection of seed vigour under artificial ageing conditions using two joined maize recombinant inbred line populations. Issue 6 (21st October 2014) - Ku, Lixia; Cui, Xinjian; Cheng, Fangfang; Guo, Shulei; Qi, Jianshuang; Tian, Zhiqiang; Han, Tuo; Ren, Zhenzhen; Zhang, Liangkun; Su, Huihui; Chen, Yanhui; Lübberstedt, T.
Abstract Seed vigour plays an important role in agricultural production, and seeds with high sowing quality are necessary for improving agriculture production. In our study, two connected maize recombinant inbred line (RIL) populations derived from Yu82 × Shen137 and Yu537A × Shen137 crosses were evaluated for the mean germination time (MGT) and other related traits under three artificial ageing treatments. We used meta‐analysis to integrate genetic maps and identify quantitative trait loci (QTLs) across the two populations. In total, 74 QTLs and 20 meta‐QTLs (mQTLs) were identified. Four key mQTLs, mQTL2‐2, mQTL5‐4, mQTL6 and mQTL8, which contained initial QTLs with R2 values >10% and included 5–9 initial QTLs, may be hot spots of important QTLs for the associated traits. Twenty‐two key candidate genes associated with four seed vigour‐related traits mapped to 14 mQTLs. In particular, the GRMZM2G163749, GRMZM2G122172/GRMZM2G554885/GRMZM2G122871 and GRMZM2G150367 genes mapped within the important mQTL5–4, mQTL6 and mQTL8 regions, respectively. Fine mapping for the genetic regions of these three mQTLs merits further study and could be utilized for marker‐assisted breeding.